EFEKTIVITAS PERSIDANGAN ONLINE DI TENGAH PANDEMI DI PENGADILAN NEGERI PEKANBARU DALAM HUKUM ACARA PIDANA - Romadansyah Romadansyah; Evi Deliana; Erdiansyah Erdiansyah (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2022)
Online trial is not a new breakthrough in the world of Indonesian law. The presence ofan online trial mechanism is currently in the background with the arrival of a 2019 coronavirus pandemic. The implementation of an online trial via teleconference is seen as in linewith government policies to carry out social distancing and physical distancing, in order tosuppress the pace of development of the Covid-19 pandemic. However, the implementation ofonline trials which were carried out simultaneously in all district courts in various placeswithout conducting any testing caused various problems. The purpose of writing this thesis isto find out the effectiveness of online trials in the midst of a pandemic at the PekanbaruDistrict Court in criminal procedural law, and what obstacles were encountered in onlinetrials in the midst of a pandemic at the Pekanbaru District Court in criminal procedural law.This research is classified in the type of sociological legal research which is engaged inthe field of legal reality, on the das sein aspect of law. Sources of data are primary data andsecondary data consisting of primary legal materials, secondary legal materials and tertiarylegal materials. Data collection techniques in this study were observation, interviews, andliterature study.The results that can be obtained from the results of this study are that in theimplementation of the online trial there are various obstacles that hinder the effectiveness ofthe online trial, impacting the rights of the suspect/defendant who are harmed. Online trial isan option to continue to provide justice in the midst of a pandemic, on the other hand justiceis not obtained by the suspect/defendant whose rights have been harmed. The obstaclesencountered in the online trial are in the form of an unstable network, inadequateinfrastructure. In addition, in the implementation of the online trial there are also actions thatharm the rights of the suspect/defendant.Key Words: Criminal Procedural Law- Online Trial- Pandemic